1995
DOI: 10.1038/bjc.1995.501
|View full text |Cite
|
Sign up to set email alerts
|

Intrapleural administration of interleukin 2 in pleural mesothelioma: a phase I-II study

Abstract: S_mmary Twenty-three patients with pleural mesothelioma stage I-IIA were entered in a study of continuous daily intrapleural infusion of interleukin 2 (IL-2) for 14 days, repeated every Intrapleural IL-2 levels were high (>20 000 IU ml-') at levels E and F, while serum levels in most patients were not or barely detectable (<3-30 IU ml-'). Intrapleural IL-2 levels were up to 6000-fold higher than systemic levels. Intrapleural tumour necrosis factor alpha (TNF-a) levels varied greatly and did not correlate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
47
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(49 citation statements)
references
References 18 publications
1
47
0
1
Order By: Relevance
“…A number of investigators have translated some of these animal findings into clinical trials. Several published phase I and II clinical trials have documented mesothelioma tumor responses to intrapleural infusion of IL-2, IFN-␤, and IFN-␥ (36,(41)(42)(43)(44). Given this potential to respond to immunologic therapy, we therefore hypothesized that the neutralization of TGF-␤ could be effective for treatment of MM in terms of release from immunosuppressive environment and normalization of host immune surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…A number of investigators have translated some of these animal findings into clinical trials. Several published phase I and II clinical trials have documented mesothelioma tumor responses to intrapleural infusion of IL-2, IFN-␤, and IFN-␥ (36,(41)(42)(43)(44). Given this potential to respond to immunologic therapy, we therefore hypothesized that the neutralization of TGF-␤ could be effective for treatment of MM in terms of release from immunosuppressive environment and normalization of host immune surveillance.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced levels of IL-2 have been associated with a lower survival of metastatic cancer patients (Herberman, 1984;Lissoni et al, 1991), and numerous trials have been performed using IL-2 alone or in combination with other forms of immunotherapy and chemotherapy (Grande et al, 2006). Several studies have shown an anti-tumoural activity of intra-pleural administration of IL-2 for the treatment of MPM, supporting the use of IL-2 in clinical trials (Goey et al, 1995;Astoul et al, 1998;Castagneto et al, 2001;Mulatero et al, 2001;Lucchi et al, 2007). However, the mechanism underlying the effects of IL-2 in the modification of the MPM microenvironment is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Intravenous, subcutaneous or intra-pleural administration of IL-2 has shown some effects on tumour regression in MPM, supporting the use of IL-2 in clinical trial settings (Goey et al, 1995;Astoul et al, 1998;Castagneto et al, 2001;Mulatero et al, 2001;Lucchi et al, 2007). However, the mechanism underlying the biological effects of IL-2 on tumour growth is complex and it is still largely unknown.…”
mentioning
confidence: 99%
“…19 Moreover, clinical trials with intrapleural IL-2 administration have been conducted for mesothelioma, and other tumors, and have yielded encouraging results. [20][21][22][23] In our study, six mesothelioma patients were treated with the vaccinia virus recombinant. No systemic or local toxicities were observed, and, despite antibody responses, vaccinia virus-IL-2 mRNA gene expression persisted in tumor biopsies for up to 3 weeks.…”
Section: Mesothelioma Gene Therapy Trials: the First Lessonsmentioning
confidence: 99%